The transcription factor VAX1 in VIP neurons of the suprachiasmatic nucleus impacts circadian rhythm generation, depressive-like behavior, and the reproductive axis in a sex-specific manner in mice - Van Loh, Brooke M.; Yaw, Alexandra M.; Breuer, Joseph A.; Jackson, Brooke; Nguyen, Duong; Jang, Krystal; Ramos, Fabiola; Ho, Emily V.; Cui, Laura J.; Gillette, Dominique L. M.; Sempere, Lorenzo F.; Gorman, Michael R.; et al. (Frontiers in Endocrinology, 2023)
Background The suprachiasmatic nucleus (SCN) within the hypothalamus is a key brain structure required to relay light information to the body and synchronize cell and tissue level rhythms and hormone release. Specific subpopulations of SCN neurons, defined by their peptide expression, regulate defined SCN output. Here we focus on the vasoactive intestinal peptide (VIP) expressing neurons of the SCN. SCN VIP neurons are known to regulate circadian rhythms and reproductive function. Methods To specifically study SCN VIP neurons, we generated a novel knock out mouse line by conditionally deleting the SCN enriched transcription factor, Ventral Anterior Homeobox 1 (Vax1), in VIP neurons (Vax1Vip; Vax1fl/fl:VipCre). Results We found that Vax1Vip females presented with lengthened estrous cycles, reduced circulating estrogen, and increased depressive-like behavior. Further, Vax1Vip males and females presented with a shortened circadian period in locomotor activity and ex vivo SCN circadian period. On a molecular level, the shortening of the SCN period was driven, at least partially, by a direct regulatory role of VAX1 on the circadian clock genes Bmal1 and Per2. Interestingly, Vax1Vip females presented with increased expression of arginine vasopressin (Avp) in the paraventricular nucleus, which resulted in increased circulating corticosterone. SCN VIP and AVP neurons regulate the reproductive gonadotropin-releasing hormone (GnRH) and kisspeptin neurons. To determine how the reproductive neuroendocrine network was impacted in Vax1Vip mice, we assessed GnRH sensitivity to a kisspeptin challenge in vivo. We found that GnRH neurons in Vax1Vip females, but not males, had an increased sensitivity to kisspeptin, leading to increased luteinizing hormone release. Interestingly, Vax1Vip males showed a small, but significant increase in total sperm and a modest delay in pubertal onset. Both male and female Vax1Vip mice were fertile and generated litters comparable in size and frequency to controls. Conclusion Together, these data identify VAX1 in SCN VIP neurons as a neurological overlap between circadian timekeeping, female reproduction, and depressive-like symptoms in mice, and provide novel insight into the role of SCN VIP neurons.